The molecular evolution of complexity at the origin of life - Dhar, Nisha (My University, 2016)
A widely accepted hypothesis for the origin of life is that it was based on catalytic RNA or ribozymes (the RNA world hypothesis). In this paradigm, one of the earliest and essential functions for an RNA based life to emerge was polymerisation. Although polymerisation activity has been demonstrated in extant and engineered ribozymes, these molecules are large and too complex to have formed spontaneously in the prebiotic world. Furthermore, the evolution and stability of RNA based life would have required a pool of diverse complex ribozymes. An understanding of the basic mechanistic processes implicated in the emergence of a minimal polymerase and diverse complex molecules from small oligomers remains a major gap. This project examined the ligation activity of a polymerase and its smaller derivatives with random oligonucleotide substrates and revealed how the molecular dynamics of ligation would have affected the evolution of complexity in the early stages of an RNA world. The size and structural complexity of a minimal polymerase (called R18 polymerase ribozyme) was reduced in a stepwise fashion. All RNA constructs were examined for self-ligation function with 24 random oligonucleotide substrates (each 35 nucleotides long) in the absence of experimentally designed base pairing. The smallest element (40 nucleotides long) was able to non-specifically ligate substrates to its own end, however, with low efficiency. A gradual increase in specificity for the substrates and overall functional efficiency was observed with an increase in structural complexity of the ribozymes. The most complex R18 polymerase ligated only selected substrate variants to itself, although with much greater efficiency than the smaller constructs. These findings suggest that the complexity in a primitive molecular system increased in a modular fashion via ligases. Furthermore, general compatibility of the ligases with the substrates was a mechanism for increase in the molecular complexity and functionality. The inverse correlation between functional flexibility and efficiency with increase in structural complexity of the catalysts points to a molecular trade-off. In the ecology of the RNA world, this molecular trade-off would have been central to ribozyme population stability and for the development of functional specialisation. The findings in this project point to a form of hypercycle composed of a complementary set of processes stabilised by inherent molecular trade-offs. Such a hypercycle is suggested to facilitate the emergence of a stable molecular network and a replicative unit essential for life to begin.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg, 2016
Keywords: Evolution, Molecular; RNA, Catalytic; Polymerization